Differential Response of Landrace-based Populations and High Yielding Varieties of Pearl Millet in Contrasting Environments - Yadav, O P; R, E Weltzien (Annals of Arid Zone, 2016)
Five populations of pearl millet (Pennisetum glaucum), having varying degrees of landrace germplasm from Rajasthan in their parentage, were evaluated across a range of environments differing greatly in their productivity levels. The populations showed different response patterns to environments with different productivity potentials. Comparison of landrace-based populations with high yielding control cultivars showed that the productivity of landrace populations for both grain and stover yields was clearly superior in low-yielding environments. In contrast, their productivity was often inferior to that of released high yielding varieties in more productive environments. Two populations, Early Rajasthan Population (ERajPop) and Early High Tillering Population (EHiTiP), flowered earlier than the early control, ICTP 8203. The landrace-derived populations had significantly higher tillering potential than the elite controls and also had more stable flowering time and tillering than high yielding controls in stress environments. Based on these results, the potential use of these landrace-based populations in future pearl millet breeding programmes is discussed. In addition, the breeding history of all populations has been briefly documented to give an overview of selection procedures followed in developing them.